2019
DOI: 10.4187/respcare.06981
|View full text |Cite
|
Sign up to set email alerts
|

Initial Noninvasive Oxygenation Strategies in Subjects With De Novo Acute Hypoxemic Respiratory Failure

Abstract: BACKGROUND: De novo hypoxemic respiratory failure is defined as significant hypoxemia in the absence of chronic lung disease such as COPD, and excluding respiratory failure occurring in the immediate postoperative or postextubation period. We aimed to evaluate the efficacy of various oxygenation strategies including noninvasive ventilation (NIV), high-flow nasal cannula (HFNC), and conventional oxygen therapy in patients with de novo hypoxemic respiratory failure. METHODS: We performed electronic database sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…An open RCT of bubble CPAP for children with severe pneumonia and hypoxemia in Bangladesh also showed that there was no difference in treatment failure between patients in the bubble CPAP group and the HFNC group (24). A review of initial non-invasive oxygenation strategies in patients with de novo acute hypoxemic respiratory failure included 16 studies, and it found that non-invasive ventilation (NIV) was associated with a significant reduction in intubation rates compared with conventional oxygen therapy, but there was no significant difference in the efficacy with HFNC (25). These findings are consistent with our research results, but the results are different from those of the meta-analysis of HFNC vs. CPAP in children with respiratory distress (18).…”
Section: Discussionmentioning
confidence: 99%
“…NIV has played a crucial role in COPD‐exacerbation management compare to standard O 2 therapy. The rate of tracheal intubation, mortality rate, and ICU stay significantly improved by employing NIV 13,17 . However, there are some limitations corresponded to NIV that should be addressed.…”
Section: Discussionmentioning
confidence: 99%